Pengaruh Suplementasi dan Proteksi Minyak Biji Kapuk Terhadap Fermentabilitas Ruminal Rumput Gajah pada Sapi Secara In Vitro - D. D. Dinata; Widiyanto Widiyanto; Retno Iswarin Pujaningsih (Jurnal Agripet, 2015)
(The effect of supplementation and protection of kapok seed oil on in vitro ruminal fermentability of elephant grass)ABSTRACT. The purpose of this research was to study the interaction between supplementation and protection of kapok seed oil (KSO) influence on in vitro digestibility and ruminal fermentability products of elephant grass. Material used were elephant grass, kapok seed oil, KOH and CaCl2 reagens and cattle rumen fluids. Completely randomized design (CRD) was used with two factorial pattern 3 x 5 with 2 replications, first factor was supplementation of KSO consist of 3 levels: 5% (S1); 10% (S2); and 15% (S3), respectively. Second factor was protection consist of 5 levels: 0% (P0); 25% (P1); 50% (P2); 75% (P3) and 100% (P4); also control treatment without supplementation and protection of KSO (S0P0). The result of this research showed there was no interaction between supplementation and protection of KSO on digestibility of elephant grass. The highest In vitro Dry Matter Digestibility (IVDMD) and In vitro Digestibility of Organic Material (IVDOM) reached by control treatment, 55,17% and 54,27%, respectively. The results of this research showed influence of interaction between supplementation and protection of KSO on VFA and NH3 production (P0.05). The highest VFA and NH3 production reached by 10% supplementation and 25% protection were 152,5 and 6,50 mM. The conclusion of this study showed that supplementation and protection of KSO was not effecting ruminal fermentation, but decreasing in vitro digestibility of elephant grass.